Feeding state regulates pheromone‐mediated avoidance behavior via the insulin signaling pathway in Caenorhabditis elegans. (19th June 2018) - Ryu, Leesun; Cheon, YongJin; Huh, Yang Hoon; Pyo, Seondong; Chinta, Satya; Choi, Hongsoo; Butcher, Rebecca A; Kim, Kyuhyung
Abstract: Animals change sensory responses and their eventual behaviors, depending on their internal metabolic status and external food availability. However, the mechanisms underlying feeding state‐dependent behavioral changes remain undefined. Previous studies have shown that Caenorhabditis elegans hermaphrodite exhibits avoidance behaviors to acute exposure of a pheromone, ascr#3 (asc‐ΔC9, C9). Here, we show that the ascr#3 avoidance behavior is modulated by feeding state via the insulin signaling pathway. Starvation increases ascr#3 avoidance behavior, and loss‐of‐function mutations in daf‐2 insulin‐like receptor gene dampen this starvation‐induced ascr#3 avoidance behavior. DAF‐2 and its downstream signaling molecules, including the DAF‐16 FOXO transcription factor, act in the ascr#3‐sensing ADL neurons to regulate synaptic transmission to downstream target neurons, including the AVA command interneurons. Moreover, we found that starvation decreases the secretion of INS‐18 insulin‐like peptides from the intestine, which antagonizes DAF‐2 function in the ADL neurons. Altogether, this study provides insights about the molecular communication between intestine and sensory neurons delivering hunger message to sensory neurons, which regulates avoidance behavior from pheromones to facilitate survival chance. Synopsis: Feeding state modulates ascr#3 pheromone avoidance behavior of Caenorhabditis elegans via an interplay between DAF‐2 insulin‐like receptor/DAF‐16 FOXO signaling axis in ascr#3 sensing ADL neurons, and regulation of intestinal secretion of the DAF‐2‐inhibitory insulin‐like peptide INS‐18. Starvation increases ascr#3 avoidance behavior. DAF‐2 insulin‐like receptor acts in the ascr#3‐sensing ADL neurons to regulate synaptic transmission to downstream target neurons. Starvation decreases the secretion of INS‐18 insulin‐like peptides from the intestine, which antagonizes DAF‐2 function in the ADL neurons. Abstract : Starvation increases ascr#3 pheromone avoidance as a result of communication between ascr#3 sensory neurons and intestinal cells.